Analysis of Vowel Formants and Frequencies for Cognitive Health Assessment: A Preliminary Study - Kevin Kristian; Bryan Santoso; Novelya Indrawan; Nicholas Hardi; Djoko Setyanto; Hadi Sutanto; Yvonne Suzy Handajani; Yuda Turana (AKSONA, 2026)
Highlight: Voice parameters did not differ between cognitive impairment groups Combined speech analysis may better assess cognition than voice alone.   ABSTRACT Introduction: Recent studies have shown that, in addition to being cost-effective and non-invasive, voice and speech analysis may play an important role in detecting cognitive impairment, such as dementia. Although numerous studies have investigated this topic, the relationship between voice-related abnormalities and cognitive impairment has not been completely captured. Objective: To investigate the relationship between voice-related abnormalities and cognitive impairment. Methods: A total of 100 participants aged >60 years were selected through purposive sampling. Cognitive function was assessed using the Indonesian version of the Montreal Cognitive Assessment (MoCA-INA), and participants were divided into cognitive impairment and non-cognitive-impairment groups. Acoustic analysis of sustained vowels was conducted using audio analysis software, focusing on formant frequencies, formant centralization ratio, fundamental frequency, and amplitude. Data were analyzed using an independent-samples t-test. Results: The cognitive impairment group demonstrated lower mean values for most formant frequencies. However, no statistically significant differences (p > 0.05) were observed between the groups in formant frequencies, formant centralization ratio, fundamental frequency, or amplitude. Conclusion: No significant association was found between voice-related abnormalities and cognitive impairment. However, subtle variations in voice parameters may still indicate other underlying neurological problems.